R(+)-Baclofen, but Not S(−)-Baclofen, Alters Alcohol Self-Administration in Alcohol-Preferring Rats - Lorrai, Irene; Maccioni, Paola; Gessa, Gian Luigi; Colombo, Giancarlo (Frontiers in Psychiatry, 2016)
Racemic baclofen [(±)-baclofen] has repeatedly been reported to suppress several alcohol-motivated behaviors, including alcohol drinking and alcohol self-administration, in rats and mice. Recent data suggested that baclofen may have bidirectional, stereospecific effects, with the more active enantiomer, R(+)-baclofen, suppressing alcohol intake and the less active enantiomer, S(-)-baclofen, stimulating alcohol intake in mice. The present study was designed to investigate whether this enantioselectivity of baclofen effects may extend also to the reinforcing properties of alcohol in rats. To this end, selectively bred Sardinian alcohol-preferring (sP) rats were initially trained to lever-respond on a Fixed Ratio (FR) 4 (FR4) schedule of reinforcement for alcohol (15%, v/v) in daily 30-min sessions. Once responding had stabilized, rats were tested with vehicle, (±)-baclofen (3 mg/kg), R(+)-baclofen (0.75, 1.5, and 3 mg/kg), and S(-)-baclofen (6, 12, and 24 mg/kg) under the FR4 schedule of reinforcement. Treatment with 3 mg/kg (±)-baclofen reduced the number of lever-responses for alcohol and estimated amount of self-administered alcohol by approximately 60% in comparison to vehicle treatment. R(+)-baclofen was approximately twice as active as (±)-baclofen: treatment with 1.5 mg/kg R(+)-baclofen decreased both variables to an extent similar to that of the decreasing effect of 3 mg/kg (±)-baclofen. Conversely, treatment with all doses of S(-)-baclofen failed to affect alcohol self-administration. These results (a) confirm that non-sedative doses of (±)-baclofen effectively suppressed the reinforcing properties of alcohol in sP rats and (b) apparently do not extend to operant alcohol self-administration in sP rats the capability of S(-)-baclofen to stimulate alcohol drinking in mice.